Simulation Analysis of Breast Cancer Screening Coverage Rate Promotion Strategies Based on System Dynamics - WANG Yanbo, ZHOU Jiangtao, WANG Bingyi, LU Wenli (Zhongguo quanke yixue, 2024)
Background The low coverage rate of breast cancer screening has affected the prevention and control effect of breast cancer in China. Factors related to the screening coverage rate include multiple aspects of the screening implementation process. Objective Based on the implementation process of breast cancer screening in China, this study aims to simulate the changes in the breast cancer screening coverage rate before and after the implement optimization measures to provide suggestions for optimizing the breast cancer screening coverage rate in China. Methods From July to September 2022, we systematically searched the journal literature on female breast cancer screening in four databases, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI) and Wanfang Data to collate and summarize the relevant influencing factors of women's screening behaviors. Collating and analysing the breast cancer screening pathways and systematic subjects of breast cancer screening in China based on the official documents of the relevant governmental websites on breast cancer screening. Based on China's breast cancer screening pathways, screening subjects and screening behavioral correlates, we constructed the causality diagram of the breast cancer screening coverage and the stock flow diagram of the system dynamics of the breast cancer screening coverage. Simulating the effects of some optimisation strategies for breast cancer screening coverage in China, 2010-2040. Results The model simulates previous screening strategies and policy resource environment. Breast cancer screening coverage gradually increased to 40% between 2010 and 2013. From 2013 to 2040, it fluctuates between 40% and 45%, showing a trend of slow decline at first and then a slow rise. Policy intervention scenarios, based on the improved population's screening intention and screening accessibility strategy, respectively simulated five kinds of optimization measures of breast cancer screening coverage rate from 2024. The five measures are as follows: (1) focusing on publicity and education, (2) standardizing the quality of screening services, (3) controlling per-case screening costs, (4) doubling the number of special breast cancer screening slots, (5) standardizing the quality of screening services and controlling per-case screening costs. The measure of focusing on publicity and education will increase rapidly coverage rate during 2024-2030 to 60.38%, then increase slowly to 66.04% during 2031-2040. The screening coverage rate will rapidly increase to 60.27% before 2029, after standardizing the quality of screening services. Then it will slowly increase to 66.04% from 2030 to 2040. After controlling per-case screening costs, the screening coverage rate will increase from 46.95% to 54.17% in 2024-2026. Then the screening coverage rate up to 58.95% in 2027-2040. Compared with no optimization measures during 2024-2040, doubling the number of special breast cancer screening slots will only increase the screening coverage rate by 1%-2%. The screening coverage rate in 2024-2040 increased from 46.95% to 86.79%, after standardizing the quality of screening services and controlling per-case screening costs. Conclusion Breast cancer screening coverage is projected to fluctuate from 41.7% to 46.0% in China from 2024 to 2040. Improving screening intention or accessibility can improve screening coverage, but the two optimization measures have their own upper limits. Meanwhile, in the Chinese population, the optimization measures to improve screening intention are better than the optimization measures to improve screening accessibility. Combined optimization measures to improve population's screening intention and screening accessibility can break through the upper limit of their respective promotion and have a better effect on improving screening coverage.